A historical perspective on peripheral reflex cardiovascular control from animals to man. Issue 8 (30th June 2014) - Sleight, Peter
<x xml:space="preserve">Abstract</x> New Findings What is the topic of this review? This review concerns the history of baroreflex control of blood pressure in animals and man. It deals mainly with mechanisms at a subcortical level and so complements the earlier review by Coote (2007). What advances does it highlight? New studies now confirm that the arterial baroreflex does control long‐term level of blood pressure through mechanisms which involve electrolyte and water excretion via nervous control of the kidney. The review also describes recent data on human blood pressure control using implanted devices to unilaterally stimulate the carotid baroreceptors, effective over several years with minimal complications. Music therapy is also discussed. Although drug treatment of human hypertension has greatly improved, there is renewed interest in non‐drug methods of blood pressure reduction. Animal experiments have now shown that arterial baroreflexes do control long‐term blood pressure levels, particularly by nervously mediated renal excretion of sodium and water. This Paton Lecture provides a review of the historical development of knowledge of peripheral circulatory control in order to supplement prior Paton Lectures concerned with cerebral cortical and other areas of influence. I also discuss how improved understanding of nervous control of the circulation has led to current methods of non‐drug blood pressure control in man by implanted carotid baroreceptor pacemakers or by renal denervation. Finally, the role of other therapy, particularly listening to music, is reviewed.